Developmental expression of mGlu2 and mGlu3 in the mouse brain - McOmish, Caitlin E. (Gene Expr Patterns, 2016)
The glutamatergic system directs central nervous system (CNS) neuronal activity and may underlie various neuropsychiatric disorders. Glutamate transmits its effects through multiple receptor classes. Class II metabotropic glutamate receptors, mGlu2 and mGlu3, play an important role in regulating synaptic release of different neurotransmitter systems and consequently modulate signaling across several neuronal subtypes. Drugs targeting mGlu2 and mGlu3 are seen as potential therapeutics for various psychiatric and neurological disorders, and defining their expression through development can aid in understanding their distinct function. Here, non-radioactive in situ hybridization was used to detect mGlu2 and mGlu3 mRNA in the CNS of 129SvEv mice at PN1, PN8, PN25, PN40, and PN100. At PN1, mGlu2 and mGlu3 are strongly expressed cortically, most notably in layer III and V. Subcortically, mGlu2 is detected in thalamic nuclei; mGlu3 is highly expressed in the striatum. By PN8, the most notable changes are in hippocampus and cortex, with mGlu2 densely expressed in the dentate gyrus, and showing increased cortical levels especially in medial cortex. At PN8, mGlu3 is observed in cortex and striatum, with highest levels detected in reticular thalamic nucleus. At PN25 patterns of expression approximated those observed across adulthood (PN40 & PN100): mGlu2 expression was high in cortex and dentate gyrus while mGlu3 showed expression in the reticular thalamic nucleus, cortex, and striatum. These studies provide a foundation for future research seeking to parse out the roles of mGlu2 from mGlu3, paving the way for better understanding of how these receptors regulate activity in the brain.